ANALISIS PENGARUH MUZARAâAH TERHADAP PENDAPATAN PETANI PENGGARAP (Studi Kasus Di Pondok Modern Gontor Kecamatan Mantingan Kabupaten Ngawi) - , andi triyawan, Dr. Soeratno ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study analyzes the effect on income tenants muzara'ah of case studies in modern cottage district Gontor Mantingan ngawi district. Necessary data in this study were primary and secondary data. Primary data obtained through interviews with rice farmers in sub-district Mantingan ngawi by using a list of questions that have been provided. Secondary data was collected from various sources that is relevantagencies. Analysis tools used to determine the factors affecting farmers incomes are multiple linear regression. Dependent variable is the production of rice, while the independent variable is the land area, number of seeds, fertilizer amount, the amount of pesticides and HOK (person-days). To find the average income per hectare of land farmers, used cost function analysis, to determine the factors that affect income farmers used simple linear regression. Dependent variable is the income while the independent variable is the production. From the analysis of the factors that affect rice production is obtained that the area of land, seed, fertilizer, pesticides and HOK jointly have a significant effect on rice production. That the use of production factors such land, fertilizer and pesticides showed positive and significant effect on rice production, while the use of production factors such Seed and HOK showed no significant effect. These factors together showed a significant effect on rice production. Average land to expand production at one time the plant is 6123 kg / ha. From the analysis of data, known to the average revenue yield of the rice paddies are 18.369.000/ha reduced total cost of planting one of 7.801.716,63/ha, we got the result of 10.567.283,37. because it uses the system muzara'ah the results are shared with the foundation so that the two net income of farmers amounted to Rp. 5.283.641,685/ ha. The results of data analysis influence the productivity of smallholder farmers net income showed a positive and significant impact on net income of farmers.